Gamification and Evaluation the Use of the Function Points Analysis Technique in Software Quality Subjects: The Experimental Studies - Santos, E. D.; Oliveira, Sandro Ronaldo Bezerra (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
With the development of new technologies at all times and the increase of competition among organizations, it is essential that they seek to achieve quality in the development of their applications. An essential tool for this is Function Point Analysis (FPA). This makes it important for students to have contact with this technique as early as possible. Thus, this study aims to use the concepts of gamification to stimulate the support for teaching and engaging students' motivation in the subject of Software Quality taught in the graduate course in computer science at UFPA. For this, classes were defined to teach the FPA technique that used elements of games as motivation for the students. Therefore, this research resulted in an enrichment of the knowledge of these students in the practice of estimation, commonly present and recommended the use in software quality models, such as MR-MPS-SW. This work focuses on contributing to the teaching of the FPA technique for students, aiming at a better preparation for the software development market. It was also verified that the use of gamification elements for the teaching of this estimation technique was efficient, since the participating students were more dedicated to the tasks and were participative in all the different types of classes.